2011
DOI: 10.1039/c1nj20523d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of novel water-soluble ligands for the complexation of metals during the partitioning of actinides

Abstract: Different types of water-soluble ligands were synthesized and their capability was evaluated by solvent extraction studies to complex trivalent actinides and suppress their extraction by a strong lipophilic ligand, such as TODGA. The back extraction efficiency of hydrophilic diglycolamide (DGA) derivatives with a varying number of ethylene glycol groups, or containing sodium acetate moieties on the amidic nitrogen shows a decrease in back-extraction efficiency with increasing number of ethylene glycol units on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…In spite of this, their selectivities are not high enough for thorium separation over either uranium or rare earth [23,24]. In order to improve the selectivity, a kind of amides derived from aminopolycarboxylate ligands, such as ethylenendiamine tetraacetic acid (EDTA), nitrilotriacetic acid (NTA) and diethylenetriamine pentacetic acid (DTPA), have been explored for actinides separation [25][26][27]. Among them, those based on NTA with special tripod structure were paid more attention.…”
Section: Introductionmentioning
confidence: 98%
“…In spite of this, their selectivities are not high enough for thorium separation over either uranium or rare earth [23,24]. In order to improve the selectivity, a kind of amides derived from aminopolycarboxylate ligands, such as ethylenendiamine tetraacetic acid (EDTA), nitrilotriacetic acid (NTA) and diethylenetriamine pentacetic acid (DTPA), have been explored for actinides separation [25][26][27]. Among them, those based on NTA with special tripod structure were paid more attention.…”
Section: Introductionmentioning
confidence: 98%
“…N,N,N',N',N",N"-hexa-n-octylnitrilotriacetamide (HONTA, Figure 1c) are alternative 'green' CHON type ligands where three acetamide groups are appended onto a central nitrogen atom to form a tripodal ligand structure with both hard (O) and soft (N) donor atoms. Though the extractant was first reported by Iqbal et al [18,19] a subsequent study by Sasaki et al, used HONTA solutions in n-dodecane and indicated selective extraction of Am and Cm with respect to lanthanides at lower nitric acid concentrations. [20] They also reported high extraction of Pu and other relevant fission product elements such as Mo, Tc, and Pt group metals.…”
Section: Introductionmentioning
confidence: 99%
“…The lipophilic ligands are typically used to extract f-block elements from highly acidic radioactive waste solutions, while the water-soluble complexants are applied to strip metal ions back. 25 Pyridine-based ligands, picolinamides for instance, are known to lose their extraction ability significantly at a pH < 3, due to protonation of the pyridine nitrogen. 25 Pyrazine will be less acid sensitive, since the pyrazine nitrogen ( pK b , pyrazine = 13.8) is much less basic than that of pyridine ( pK b , pyridine = 8.8).…”
Section: Synthesis Of Pyrazine-based Lanthanide/actinide Ligandsmentioning
confidence: 99%